Analyzing the factors for implementation of green supply chain management. Issue 3 (16th May 2016) - Singh, R.K.; Rastogi, Sanjay; Aggarwal, Mallika
Abstract : Purpose: In the present context of a globalised economy, market requirements are changing regularly in term of product cost, delivery time, safety and environmental issues. Apart from conventional measures, environmental factors have become an integral part of performance measurement system. This study aims to analyse major barriers and factors in green supply chain (GSC) management implementation. Design/methodology/approach: The present study has tried to identify barriers and factors for green supply chain management (GSCM) based on literature review. Factors for GSCM have been modelled by interpretive structural modelling (ISM) approach. Findings: Based on literature review, 12 factors have been identified. It has been observed that top management commitment, integration among supply chain members, vendors' development, environmental friendly packaging and transportation, reverse logistic management and development of a green performance measurement system are major drivers for successful implementation of GSCM. Research Limitations/implications: Organisations need to follow a proactive approach for taking GSC initiatives. For generalisation of findings, empirical study and some case studies need to be carried out. Originality/value: Findings of this study will help organisations in strategy formulation for GSCM and successful implementation for sustainable competitiveness.